Evaluation of the Implementation of the Occupational Safety and Health Management System (SMK3) at Dr. H. Bob Bazar Hospital, Indonesia - Harum, Ayu Pandan (Golden Ratio of Data in Summary, 2025)
International demands and competition have made occupational safety and health (OHS) a very important global issue. Related to the data report at Dr. H. Bob Bazar Hospital, there were work accidents to officers and accidents to patients. The purpose of this study was to determine the Occupational Safety and Health Management System at Dr. H. Bob Bazar Hospital in 2024. This study is a type of qualitative research. The informants of this study consisted of 5 people including 1 person in charge of OHS, 1 Head of Medical Support Section, 3 OHS officers. With the key informant in charge of OHS, the main informant is the Head of Medical Support Section, and the supporting informant is the OHS officer. Data collection through interview and observation methods conducted in August 2024. The results of this study indicate that Dr. H. Bob Bazar Hospital. Dr. H. Bob Bazar Hospital has had a K3RS policy but in its implementation, it has not been implemented properly according to PMK 66 of 2016. The existing K3 human resources have not been able to fully cover K3RS activities. Health services with health checks for officers have never been carried out. Preparedness has been carried out in dealing with emergency conditions and disasters with evacuation routes and APAR. Dr. H. Bob Bazar can increase resources and communication for K3RS implementation. Apart from that, we also carry out supervision and evaluation on the implementation of hospital SMK3 at least once a year so that implementation is more measurable and effective.